The effect of gender-specific invitation letters on utilization of colorectal cancer screening = Der Einfluss von geschlechtsspezifischen Einladungsschreiben auf die Inanspruchnahme von Darmkrebsvorsorgeuntersuchungen - Zhan, Tianzuo; Hielscher, Thomas; Eckardt, Maximilian; Ebert, Matthias; Belle, Sebastian (Zeitschrift für Gastroenterologie, 2019)
Background and aim Colorectal cancer (CRC) screening can effectively reduce cancer-associated mortality. In Germany, individuals over the age of 50 or 55 have access to CRC screening services. However, utilization rates are persistently low, particular in the male population. This observational study investigates the effect of standard versus gender-specific invitation letters on utilization of CRC screening services.Methods We analyzed utilization rates of individuals who were insured by a large health insurance fund in Bavaria, Germany. Persons who became eligible for CRC screening received a standard (2013-2014) or a gender-specific invitation letter (2015-2016). We compared utilization rates within 6 months after receipt of the invitation letter using billing codes of the health insurance fund. Results Invitation letters were sent to 49 535 individuals, of which 48.8 % were gender-specific. The overall utilization rate did not differ between recipients of the standard versus gender-specific invitation letter (11.6 % vs 11.1 %; RR: 0.97 [0.92-1.02], p = 0.19). However, uptake of screening colonoscopy was significantly higher among recipients of gender-specific invitations (2.9 % vs 3.5 %; RR: 1.21 [1.04-1.39], p = 0.01), whereas utilization of fecal occult blood tests declined (10.4 % vs 9.7 %; RR: 0.93 [0.88-0.99], p = 0.016). Conclusions Gender-specific design of invitation letters can modify the patients’ preference for specific CRC screening services and increase the acceptance of screening colonoscopy.
Gesehen am 02.12.2019